An edition of Oxford, Trinity College, MS 29 - Gillhammer, CC (2019)
Oxford, Trinity College, MS 29 is a late 15th-century manuscript which contains a large number of excerpts from diverse religious and secular medieval texts like the Vulgate, Caxton’s print of the Polychronicon, de Worde’s print Information for pilgrims unto the Holy Land, Chaucer’s Canterbury Tales, Peter of Poitiers’s Compendium historiae in genealogia Christi, Gower’s Confessio Amantis, a Holy Cross legend, Jacques Legrand’s Book of Good Manners, and Mandeville’s Travels. These texts are compiled in an idiosyncratic manner, forming a seamless prose history of the world, which starts with the creation of the world and ends incompletely with a description of Hannibal’s exploits. Written by a single compiler-scribe, the manuscript offers fascinating insights into methods of compilation employed by medieval historiographers at the close of the Middle Ages. Two other manuscripts in the same hand are extant – San Marino, Huntington Library, MS HM 144 and London, Lambeth Palace Library, MS 84 – which show similarities in design and compilatory technique.